Population Aging and the Emergence of New dDemands of Public Policy in Viana/ES - Anderson Silva Oliveira (Geografares, 2015)
In the area of public policies more people are reaching older ages and living longer, increasing the demand for public services creating new necessities and requiring from the municipalities an efficient and wider service which allows to the elderly people favorable conditions to have a healthy and an active life. In order to provide a humble contribution that older people have an increasingly better quality of life was developed this article featuring aging in Viana through the construction and analysis of indicators and that identifies new public policy demands that arise linked to increased participation of older people in the total population. To identify the main needs of the age group of 60 years and over a mixed questionnaire was applied to 80 elderly residents of the municipality who participate in activities in the Elderly Living Center and the de Noronha Marcilio elderly associations and Vila Betânia neighborhoods among the most aged. The greatest need according the elderly are health care and leisure facilities.